Sociology Teacher Innovation in Online Learning During the Covid-19 Pandemic in Central Lombok Regency - Septiastuti, Putu; Sukardi, Sukardi; Nursaptini, Nursaptini; Masyhuri, Masyhuri (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
The aims of this study was to determine the innovation ability of sociology teachers in teaching and learning during the Covid-19 pandemic in Central Lombok Regency in terms of school location and current conditions in Central Lombok Regency. This study uses quantitative methods to conduct survey research. All 50 sociology teachers who participated in this study constituted the study population. The proportionate random sampling method was applied in this investigation. All sociology teachers who have fulfilled the research requirements required by using SPSS version 26’for windows were given a questionnaire as a research instrument. Data collection techniques involving surveys and documentation. Using data analysis methods, especially comparative analysis, to test hypotheses. These findings demonstrate the innovation ability of sociology teachers to innovate during the Covid-19 outbreak, with an average school location (suburb, city, remote) and the status of public and private schools. Therefore, it can be said that the findings of this study indicate that sociology teachers in Central Lombok Regency lack the innovation abilities of sociology teachers during the Covid-19 outbreak.